2021
DOI: 10.3390/socsci10110429
|View full text |Cite
|
Sign up to set email alerts
|

Australian Health Professionals’ Attitudes toward Voluntary Assisted Dying: A Cross-Sectional Survey

Abstract: Voluntary assisted dying (VAD) is when a terminally ill person with decision-making capacity consensually ends their life with assistance from an authorised professional. Many countries have legalised VAD, and health professionals’ roles within VAD frameworks are varied. Health professionals must be well informed of their legal obligations to ensure they practice within the legal boundaries, and those professionals with objections toward VAD should ensure that their eligible patients have equitable access. Giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The key finding in the context of implementation was that Health Widespread community support for VAD (Emanuel et al, 2016;Kresin et al, 2021) has translated into law in many jurisdictions. The practise of intentionally ending a life, however, does not garner the same level of support among those healthcare services or healthcare professionals who are ultimately responsible for operationalising these laws (Emanuel et al, 2016;Munday & Poon, 2020;O'Connor et al, 2021). This means that implementing the law may face unique challenges (Fujioka et al, 2018).…”
Section: Results Summarymentioning
confidence: 99%
“…The key finding in the context of implementation was that Health Widespread community support for VAD (Emanuel et al, 2016;Kresin et al, 2021) has translated into law in many jurisdictions. The practise of intentionally ending a life, however, does not garner the same level of support among those healthcare services or healthcare professionals who are ultimately responsible for operationalising these laws (Emanuel et al, 2016;Munday & Poon, 2020;O'Connor et al, 2021). This means that implementing the law may face unique challenges (Fujioka et al, 2018).…”
Section: Results Summarymentioning
confidence: 99%
“…A systematic review of health professionals’ perspectives on AD implementation barriers and facilitators identified that personal and professional values act as both barriers and facilitators and influence how HCPs prioritise clinical issues [ 36 ]. In Australia, HCPs’ attitudes towards AD are informed by their beliefs, emotions, education, and strength of religious beliefs, but not knowledge of AD [ 37 ]. The authors of these two studies [ 36 , 37 ] advocate for more research with HCPs and stakeholders regarding ‘safeguarding’ and assessing ‘capacity’ and for HCPs’ reflexive practice about the influence of values and feelings on clinical practice [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, HCPs’ attitudes towards AD are informed by their beliefs, emotions, education, and strength of religious beliefs, but not knowledge of AD [ 37 ]. The authors of these two studies [ 36 , 37 ] advocate for more research with HCPs and stakeholders regarding ‘safeguarding’ and assessing ‘capacity’ and for HCPs’ reflexive practice about the influence of values and feelings on clinical practice [ 36 , 37 ]. Safety is a priority for respondents as referenced by items 1, 4 and 10 (see Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a new Australian study reports that health professionals with a high level of education had a more positive attitude toward assisted dying. 24…”
Section: Experience and Educationmentioning
confidence: 99%
“…Furthermore, experienced nurses working with terminally ill patients seem to vary more in their attitudes toward assisted dying. 24 In 2015, the Norwegian Bioethical Survey (NOBAS) conducted a population survey with a sample of 22,660 Norwegians that included questions about their attitudes toward assisted dying. 2 The bivariate analyses in the study showed that the majority of the participants agreed with legalizing assisted dying through physician-assisted suicide (73%, N = 2230) and euthanasia (66%, N = 2027).…”
Section: Introductionmentioning
confidence: 99%